Experimental and thermodynamic analysis of hydrogen and gasoline in a spark-ignition engine - Oktar, Hilmi Ersin; Ozkan, Muammer; Hurpekli, Mersin (PERGAMON-ELSEVIER SCIENCE LTD, 2026)
Hydrogen is a key alternative energy source, yet the literature lacks a unified experimental-modelling-optical comparison against gasoline across the full engine operating map. This study investigates both fuels in a naturally aspirated single-cylinder PFI-SI engine by performing a complete mapping at IMEP-matched and full-load conditions between 1000 and 5000 rpm. Intake, exhaust and in-cylinder crank-angle resolved pressure measurements enabled a detailed characterization of gas exchange, and normal/abnormal combustion events. Results show that hydrogen achieves up to 12.1 % higher indicated thermal efficiency than gasoline under the same IMEP conditions, although experiencing up to 18.1 % higher wall heat transfer losses. Full-load H2-PFI operation exhibited a 32-58 % power reduction due to volumetric efficiency and backfire limitations driven by elevated exhaust temperatures. By combining experimental, modelling, and optical imaging under matched load conditions, the study provides an integrated perspective on the combustion characteristics, limitations and practical boundaries of hydrogen PFI-SI engines.
Keywords: Spark-ignition engine; Hydrogen; Gasoline; Port fuel injection; COMBUSTION; PERFORMANCE; BACKFIRE; POWER; Chemistry; Electrochemistry; Energy & Fuels